Cinema Industry of China and Pakistan in the Perspective of the Belt and Road Initiative - Wei, Zhou; Iftikhar, Rukhsana (Annals of Human and Social Sciences, 2023)
Belt and Road" initiative by China, has been increasing in frequency and depth of cultural exploration between China and Pakistan. The objective of the paper is to highlight the cultural collaboration in the field of cinema between China and Pakistan after the massive development of belt and road initiative. As a crucial component of the cultural industry, cinema serves as a medium for cultural interactions between the two nations. This study delves into the exchange and collaboration of Pakistani cinema culture in China after 2013, examining the historical trajectory of Pakistani cinema exchanges in China. Furthermore, it evaluates the significant role played by Pakistani cinema in advancing cultural diplomacy and exchanges between China and Pakistan, thereby greatly contributing to the bilateral friendship and cultural ties between the two nations. The qualitative method of research is used especially examining the movies response in China. The release of Pakistani films in China and their cooperation in making of animated opened new era of joint cinema industry. This initiative in the field of cinema paved a way for exploring new arenas in cultural collaboration between China and Pakistan. More new projects would be initiated between China and Pakistan to strengthen the cultural ties between two countries.